ABOUT THE UNIFORMITY OF LEGAL TERMS - Shyngysbayeya Дуйсенкуль Мухамбетжановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article deals with the problems of the uniformity of legal terms.